2023
DOI: 10.1590/1519-6984.265991
|View full text |Cite
|
Sign up to set email alerts
|

Does silicon attenuate PEG 6000-induced water deficit in germination and growth initial the seedlings corn

Abstract: Water stress limits the initial growth and development of maize mass and grain, as well as the physiological process for absorbing the amount of mineral elements. The objective was to evaluate the effect of silicon on germination and growth of corn seedlings submitted to water deficit. The experiment was carried out in the laboratory and the experimental design was completely randomized (factorial 3 × 4), with three concentrations of calcium silicate (0.0; 1.0 and 2.0 mM) and 4 solutions of PEG-6000 to simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, changes in precipitation patterns, due to natural or anthropogenic effects, are triggering yield damage, particularly in arid areas [ 6 , 7 ]. Drought, as one of the most common abiotic stresses on plants in these areas, results in global yield losses of 20% for wheat [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in precipitation patterns, due to natural or anthropogenic effects, are triggering yield damage, particularly in arid areas [ 6 , 7 ]. Drought, as one of the most common abiotic stresses on plants in these areas, results in global yield losses of 20% for wheat [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to stressful environments, plants are constantly making adjustments, leading to numerous morphological, physiological, and biochemical changes, such as stomatal movement, osmotic adjustment, and reactive oxygen species (ROS)-mediated antioxidant defense system [1,3,5,6]. In recent years, plants' response to water-deficit stress has become the focus of plant-environment interaction research, and various response mechanisms operating in plants have been found [7][8][9][10][11][12]. However, it is still a major challenge to effectively apply these results to field production.…”
Section: Introductionmentioning
confidence: 99%